1990
DOI: 10.1111/j.1365-2184.1990.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony of bone marrow proliferation and maturation as the origin of cyclic haemopoiesis

Abstract: Abstract. Cyclic haemopoiesis in Grey Collie dogs is characterized by stable oscillations in all haemopoietic lineages. It is proposed that in these animals, in contrast to normal animals, the maturation process of haemopoietic (in particular granuloid) cells from the primitive progenitors to the functional cells is characterized by an abnormally strong synchrony. It is conjectured that the marrow maturation time has a very small variance compared with non‐cyclic normal dogs. With a mathematical model of haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…& van den Driessche, 1979;King-Smith & Morley, 1970;MacDonald, 1978;Morley et al, 1969;Morley & Stohlman, 1970;Morley, 1970Morley, , 1979Reeve, 1973;Schmitz, 1988;Schmitz et al, 1993Schmitz et al, , 1994Schmitz et al, , 1995Schmitz et al, , 1990Shvitra et al, 1983;von Schulthess & Mazer, 1982;Wichmann et al, 1988). However, recent modeling (Hearn et al, 1998) has shown that a destabilization of this feedback pathway cannot account for the onset of oscillations seen in CN, and concluded that CN was probably not solely due to an instability in the peripheral feedback loop.…”
Section: Haurie E¹ A¸mentioning
confidence: 91%
“…& van den Driessche, 1979;King-Smith & Morley, 1970;MacDonald, 1978;Morley et al, 1969;Morley & Stohlman, 1970;Morley, 1970Morley, , 1979Reeve, 1973;Schmitz, 1988;Schmitz et al, 1993Schmitz et al, , 1994Schmitz et al, , 1995Schmitz et al, , 1990Shvitra et al, 1983;von Schulthess & Mazer, 1982;Wichmann et al, 1988). However, recent modeling (Hearn et al, 1998) has shown that a destabilization of this feedback pathway cannot account for the onset of oscillations seen in CN, and concluded that CN was probably not solely due to an instability in the peripheral feedback loop.…”
Section: Haurie E¹ A¸mentioning
confidence: 91%
“…Two pathologies rose the attention of these two groups: chronic myelogenous leukemia in its periodic form [133] and [283], [192], both in the late 1990's, and cyclic neutropenia, starting in the middle of the 1990's too for Loeffler [265] and late 1990's for Mackey [156]. Other general cyclic hematopoietic diseases were studied [264], some with chemotherapy modeling attempts [270], [163] or treatments [142] and other hematotoxic products [260]. Few works were focused on erythropoiesis, besides some theoretical approaches from Bélair et al [54], [202], [254], [256] and some attempts to fit experimental data for anemia [189], or erythropoietin (EPO) effect [98], [101].…”
Section: The 1990's: Continuitymentioning
confidence: 99%
“…The GM-CSF feedback loop has been described in detail previously. 24,26,27 The efferent part of the G-CSF loop controls the amplification in PGP, the transit time in MGP, and the rate of cells emerging from bone marrow to the peripheral blood. The afferent part of the loop controls the present serum concentration of G-CSF.…”
Section: Model Structurementioning
confidence: 99%
“…[23][24][25][26] Figure 1 gives an overview of the model structure. The model considers human granulopoiesis as a set of compartments, each representing the population size (ie, cell number) of a distinct hematopoietic cell stage.…”
Section: Model Structurementioning
confidence: 99%
See 1 more Smart Citation